People displaced by climate change and proposal for a global convention to help them - Ansari, Abdul Haseeb; Shair Mohamad, Mohd Akram; Eishan Jan, Mohammad Naqib (Secretariat, Asian-Africal Legal Consultative Organization, New Delhi, 2010)
People are being displaced from their places of living because of adverse weather conditions, rise of sea level and desertification caused by global warming. These displaced people are either 'internally displaced people' or 'irregular migrants'. If appropriate measure is not taken to substantially reduce green house gas emissions, the number of displaced people is going to profusely increase. It is the duty of the parent state in particular, and of the international community in general, to extend them humanitarian aid and to provide facilities for sending them back to their original places of living. States, which are more responsible for the phenomenon of climate change, have to share the large part of this duty. Presently, law to deal with these displaced people is based on certain norms contained in some human right treaties and soft law. There is, thus, need to have a global convention to extend aid and other help to them. Its modality has been sketched after thorough discussions on certain important aspects and a proposed convention.